Research on the Strategy of Secondary Utilization of Environmental Protection Materials in Traditional Mountain Dwellings - Yang Yue; Chen Bin (E3S Web of Conferences)
In the context of global sustainable development, the preservation and renovation of traditional dwellings have garnered significant attention. As an important cultural heritage, the ecological protection of mountainous traditional dwellings is of great significance. This paper explores strategies for the secondary utilization of eco-friendly materials in mountainous traditional dwellings. First, through literature research, domestic and international research results on the application of eco-friendly materials were collected and analyzed. Then, a field investigation was conducted on representative mountainous traditional dwellings in China to record the usage of existing building materials and their environmental impact. Next, through interdisciplinary research, the physical and ecological performance of various eco-friendly materials, including indicators such as strength, density, durability, and carbon footprint, were evaluated, and strategies for their secondary utilization were proposed. Finally, taking the Peng’s Residence as an example, the secondary utilization of eco-friendly materials in this dwelling and the implementation effects were analyzed. The study found that the reuse of eco-friendly materials can not only reduce resource consumption and environmental impact but also enhance the ecological and economic benefits of buildings, providing new ideas and methods for the preservation and renovation of traditional dwellings.